Differences in Employee Motivation in Selected Countries of CEE (Slovakia, Lithuania and the Czech Republic) - Hitka, Miloš; Balážová, Žaneta; Gražulis, Vladimiras; Lejsková, Pavla (My University, 2018)
The level of employee motivation in the countries of Central and Eastern Europe (Slovakia, Lithuania and the Czech Republic) is analysed in the paper. Sampling unit consisted of 6,961 respondents (hereof 3,862 males and 3,009 females). The age, education, seniority and job position of respondents were various. Significance of differences of averages and standard deviation of specific motivation factors at the level of significance alpha =0.05 in terms of nationality and the age of respondents was verified in tests. Subsequently, the samples were tested using the Tukey's HSD test. Following the research, the order of 8 most important motivation factors in analysed countries was defined. The subtle difference was observed in the order of their importance. Differences are dependent on the nationality; however, they do not depend on the age. The importance of motivation factors in Lithuania differs from those in Slovakia and the Czech Republic. Basic salary, atmosphere in the workplace, supervisor's approach, fringe benefits are the most important motivation factors in all three countries. The importance of further motivation factors is almost equal in Slovakia and the Czech Republic (motivation factors relating to finances and relationships). The difference is seen in Lithuania, where the motivation factors relating to personal development and career are considered the most important. The research and its outcomes can be considered a part of further research carried out in other countries of Western, Central as well as Eastern Europe.
Rozdíly motivace zaměstnanců ve vybraných zemích střední a východní Evropy (Slovensko, Litva a Česká republika)
Keywords: Motivation; Motivation Programme; Tukey's HSD test; ANOVA; CEE; Slovakia; Lithuania; the Czech Republic; motivace; motivační program; Tukeyho HSD test; ANOVA; Slovensko; Litva; Česká republika